1972
DOI: 10.1007/bf01868107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phloretin on monosaccharide transport in erythrocyte ghosts

Abstract: Summary. 3H-labelled phloretin was shown to be bound reversibly by human erythrocyte and ghost membranes but not to penetrate across them in either direction. Kinetic parameters of D-xylose and D-galactose transport in intact cells and in ghosts, as well as the inhibition by phloretin of these transports were found to be in fair agreement. By enclosing phloretin in ghosts, its inhibition of monosaccharide transport was found to be symmetrical and thus an equivalence of the outer and the innner membrane sides o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1973
1973
1985
1985

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Phloretin is known to react rapidly, and it has been shown elsewhere (LeFevre & Marshall, 1959;Bene~, Kofinsk~i & Kotyk, 1972) that phloretin binds to the red cells immediately after it is mixed with a red cell suspension. This rapid binding has been shown to be exclusively on the membrane surface, and phloretin molecules do not penetrate the red cell after long incubation times (Bene~ et al, 1972). Our current experiments show that at "zero" incubation time, which denotes having the phloretin and nonelectrolyte together in one stopped-flow syringe and the red ceil suspension in another syringe, 0.25 m~ phloretin had essentially no effect on urea permeability; i.e., (Sphlore,in/S)~ 1.0.…”
Section: Resultsmentioning
confidence: 98%
“…Phloretin is known to react rapidly, and it has been shown elsewhere (LeFevre & Marshall, 1959;Bene~, Kofinsk~i & Kotyk, 1972) that phloretin binds to the red cells immediately after it is mixed with a red cell suspension. This rapid binding has been shown to be exclusively on the membrane surface, and phloretin molecules do not penetrate the red cell after long incubation times (Bene~ et al, 1972). Our current experiments show that at "zero" incubation time, which denotes having the phloretin and nonelectrolyte together in one stopped-flow syringe and the red ceil suspension in another syringe, 0.25 m~ phloretin had essentially no effect on urea permeability; i.e., (Sphlore,in/S)~ 1.0.…”
Section: Resultsmentioning
confidence: 98%
“…From experiments on ghosts, Ben~s et al [4] suggested that there are phloretin binding sites on both sides, but the observations are puzzling and the argument appears to be faulty: exit of xylose was inhibited by phloretin added to the external medium but not by phloretin trapped inside the ghosts, while entry was inhibited in the opposite way, i.e., by internal but not by external inhibitor. Believing, mistakenly as we now know [9,14], that phloretin cannot pass through the cell membrane, the authors concluded that transport is blocked only when the inhibitor is bound trans with respect to the substrate; but since phloretin would have had time to equilibrate [9], it should have been available on both sides, and therefore transport should have been inhibited in all cases.…”
Section: The Asymmetry Of the Glucose Carrier And Phloretin Bindingmentioning
confidence: 92%
“…According to an early report, phloretin does not penetrate the cell membrane [4] and therefore, when added to the suspending medium, could only add to the outer carrier form, regardless of whether the inner form possesses a phloretin binding site. Later studies demonstrated that it actually enters red cells rapidly and is strongly adsorbed both to the cell membrane and to hemoglobin [9,14].…”
Section: The Asymmetry Of the Glucose Carrier And Phloretin Bindingmentioning
confidence: 99%
“…It has been shown that in contrast to sugar permeability, which could be inhibited from either surface (for the sidedness of the action of the aglycone, see Bene~, Kolinskfi and Kotyk, 1972), the equilibrium exchange for halide anions (Schnell, Gerhardt, Lepke & Passow, 1973) and sulfate could only be inhibited if the agent was present on the outer surface of the membrane. In view of the demonstrated asymmetry of the effect of phlorizin on anion exchange we included into the present work an investigation of the sidedness of the effect of this modifier on net salt movements.…”
mentioning
confidence: 95%